EFFECT OF DAYS IN ONE WEEK RETURN TO STOCK LEVELS STOCK EXCHANGE IN JAKARTA - Mudjijono, Amad; Legowo, M.Si., Ak., Drs. H. Herman (Accounting, 2010)
Many people want to know today whether investors within approximately one week (five days of trading) which is expected to bring the most advantages and the day is approximately the level will experience a negative return. Investors in an investment community certainly do not want to experience the risk of loss because they try to invest approximately when they will do will not experience losses and when approximately will benefit more above the average of other days. Based on the above items that this thesis is prepared to meet the above matters. This thesis will examine the effect of day within one week of the level of stock return that occurs on the Jakarta Stock Exchange. Keywords: Return.